Quality Improvement Project on Split-Post Placement in Core Psychiatry Training - Hala Elhardlu; Faquiha Muhammad; Suneetha Siddabattuni (BJPsych Open, 2025)
Aims: Split-post placements are part of Psychiatry training, being a combination of inpatient and outpatient settings. The outpatient post could be set within the community mental health teams outpatient clinics, Crisis teams, Gender Identity and CAMHS clinics.